UTILIZATION OF LEARNING MANAGEMENT SYSTEM IN GEOGRAPHY LEARNING: A CASE STUDY OF GRADE X STUDENTS AT SMA COKROAMINOTO MADIUN, INDONESIA - Ajeng Tiara Sekaring Kusuma (CV. Radja Publika, 2026)
The rapid development of information technology has encouraged educational institutions to integrate digital learning platforms into classroom instruction. One of the most widely implemented platforms is the Learning Management System (LMS), which facilitates online learning activities, learning resource management, communication, and assessment. This study aims to describe the utilization of the Learning Management System in Geography learning for Grade X students at SMA Cokroaminoto Madiun. The research employed a qualitative approach using a case study design. Data were collected through interviews, observations, and documentation involving geography teachers, students, and school administrators. Data analysis followed the Miles and Huberman model, consisting of data reduction, data display, and conclusion drawing. Data validity was ensured through source triangulation, technique triangulation, member checking, and peer debriefing. The findings indicate that the implementation of LMS supports geography learning through the provision of digital learning materials, online assignments, discussion forums, and electronic assessments. The LMS improves students' accessibility to learning resources, encourages independent learning, strengthens communication between teachers and students, and increases students' learning motivation. Nevertheless, several challenges remain, including unstable internet connectivity, differences in students' digital literacy, and the need for more interactive learning content. The study concludes that the Learning Management System is an effective learning medium for Geography education and contributes positively to improving learning quality and student engagement.